First report of the occurrence of Trichinella-specific antibodies in domestic pigs in Central and Eastern Uganda - Roesel, Kristina; Nöckler, K.; Baumann, M.P.O.; Fries, R.; Dione, Michel M.; Clausen, Peter-Henning; Grace, Delia (Public Library of Science, 2016)
Previous research on trichinellosis in Africa focused on isolating Trichinella from wildlife while the role of domestic pigs has remained highly under-researched. Pig keeping in Uganda is historically recent, and evidence on zoonotic pig diseases, including infection with Trichinella species, is scarce. A cross-sectional survey on Trichinella seroprevalence in pigs was conducted in three districts in Central and Eastern Uganda from April 2013 to January 2015. Serum from a random sample of 1125 pigs from 22 villages in Eastern and Central Uganda was examined to detect immunoglobulin G (IgG) against any Trichinella spp. using a commercially available ELISA based on excretory-secretory antigen. ELISA positive samples were confirmed using Western Blot based on somatic antigen of Trichinella spiralis as recommended in previous validation studies. Diaphragm pillar muscle samples (at least 5 g each) of 499 pigs from areas with high ELISA positivity were examined using the artificial digestion method. Overall, 78 of all 1125 animals (6.9%, 95% CI: 5.6–8.6%) tested positive for antibodies against Trichinella spp. in the ELISA at significantly higher levels in Kamuli district compared to Masaka and Mukono districts. Thirty-one percent of the ELISA positive samples were confirmed IgG positive by the Western Blot leading to an overall seroprevalence of 2.1% (95% CI: 1.4–3.2%). The large proportion of ELISA positive samples that could not be confirmed using Western blot may be the result of cross-reactivity with other gastrointestinal helminth infections or unknown host-specific immune response mechanisms in local pig breeds in Uganda. Attempts to isolate muscle larvae for species determination using the artificial digestion method were unsuccessful. Due to the large number of muscle samples examined we are confident that even if pigs are infected, the larval burden in pork is too low to pose a major risk to consumers of developing trichinellosis. This was the first large systematic field investigation of Trichinella infection in domestic pigs in Uganda and its results imply that further studies are needed to identify the Trichinella species involved, and to identify potential sources of infection for humans.